Moderating Effects of Educational Level and Mathematical Competence on the Effectiveness of Cognitive Conflict Strategy: A Meta-Analysis - Onesimus Laia, Harun; Martadiputra, Bambang Avip Priatna; Candraningsih, Yosy; Marjud, Fujiama (Pendidikan Matematika UNIMOR, 2025)
This study aims to analyze the effectiveness of the cognitive conflict strategy in mathematics learning and to examine whether educational level and mathematical competence act as moderators in this strategy. A meta-analysis approach was conducted on 41 effect sizes. Data were analyzed using a random-effects model, with effect sizes calculated using Hedges' g. The data analysis was performed using the Comprehensive Meta-Analysis (CMA) software to ensure the accuracy of effect size calculations, heterogeneity tests, and moderator analyses. The results show that the cognitive conflict strategy has a significant effect (g = 1.047; p < 0.05). Additionally, mathematical competence was found to be a significant moderator (p < 0.05), with the highest effect sizes observed in conceptual understanding (g = 1.712) and critical thinking (g = 1.355). However, the educational level did not serve as a significant moderator (p = 0.092), indicating that the cognitive conflict strategy is beneficial across various educational levels. This study concludes that the cognitive conflict strategy is effective in enhancing mathematics learning, especially in conceptual understanding and critical thinking. Its novelty lies in identifying mathematical competence, not educational level, as a significant moderator. This implies that implementation should be adjusted based on the targeted competence. Future research may explore other potential moderators, including learner traits, instructional design, and technology use, to refine its application.